Islam sebagai Agama Masa Depan : Pandangan Masyarakat Barat terhadap Islam - Gunawan Widjaja (Al-Ulum, 2021)
This scientific work aims to find data through studies in international publications that discuss Islam as a great religion and the future in the view of the western scientific community. To facilitate the search for data to answer this research question, we first searched it from Islamic religious literature electronically to understand and answer the question with valid and reliable findings. The way we analyze involves, among other things, a data analysis system, coding the data, and drawing a summary of the final understanding according to the research question. So, based on the findings and discussion of the data, most of the publications state that Islam is the fastest-growing religion in the world today. Because it is developing so fast, it will be an essential concern for the West. They see Islam as a threat to the future of world civilization, which the West now dominates, but Islam is also a religion that they consider quantitatively and qualitatively by practicing Islamic teachings specifically. Hopefully, this finding can be a valuable contribution to many Islamic studies in the future.